A Descriptive Study of Exclusive Breastfeeding History and Nutritional Status in Toddlers Aged 12–24 Months at Tambakrejo Community Health Center, Surabaya - Maharani Bintang Pratiwi; Inne Soesanti; Riezky Faisal Nugroho; Taufiqurrahman (Journal of Nutrition Explorations, 2025)
The toddler stage is a vital period of growth when insufficient exclusive breastfeeding can lead to undernutrition, malnutrition, and stunting due to high nutritional needs and limited nutrient absorption. This descriptive study aimed to describe exclusive breastfeeding history and the nutritional status of toddlers aged 12–24 months at Tambakrejo Community Health Center, Surabaya. Conducted from October 2023 to March 2024, the study involved 49 toddlers selected from a population of 173 through simple random sampling. Data were collected through anthropometric measurements (weight-for-height Z-scores) and structured interviews with mothers. Analysis was performed using univariate descriptive statistics in SPSS. Results showed that 89.8% of toddlers had good nutritional status and 79.6% received exclusive breastfeeding. Exclusive breastfeeding was more common among mothers with senior high school education (69.4%) and those who were housewives (63.3%). A positive trend was observed between exclusive breastfeeding and good nutritional status. Future studies should involve larger samples and explore other contributing factors using analytical approaches.